Multicenter evaluation of the Luminex® ARIES® HSV 1&2 Assay for the detection of herpes simplex virus types 1 and 2 in cutaneous and mucocutaneous lesion specimens. (1st December 2016) - Young, Stephen; Body, Barbara; Moore, Franklin; Dunbar, Sherry
ABSTRACT: Introduction : The ARIES® HSV 1&2 Assay is a new FDA cleared real-time PCR test for detection and differentiation of HSV-1 and HSV-2 DNA from cutaneous and mucocutaneous lesions. The test is performed on the ARIES® System, an automated sample to answer real-time PCR instrument that provides a closed system and simple workflow for performing molecular testing. Areas covered : This article reports the clinical performance of the ARIES® HSV 1&2 Assay assessed on 1963 prospectively collected specimens. Assay sensitivities were 91.1–95% (cutaneous) and 97–98.5% (mucocutaneous), and specificities were 88.8–94.2% (cutaneous) and 93.2–95.4% (mucocutaneous), as compared to the ELVIS® HSV test system. Expert commentary : Detection of HSV DNA by PCR is rapid and more sensitive than traditional culture and immunoassay methods and is being widely adopted in many laboratory settings. Sample to answer molecular platforms like ARIES® will enable routine and non-molecular labs to perform sensitive and rapid molecular testing with ease.